1985
DOI: 10.1002/aja.1001740203
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular cells in cartilage canals of the developing mouse epiphysis

Abstract: Morphological variability among perivascular cells adjacent to cartilage matrix during the elongation of canals through both uncalcified and calcified matrix has not been reported. Cartilage canals were located in distal femoral epiphyses of 5- to 7-day-old mice and identified as vascular channels arising from perichondrial surfaces along the condyles and intercondylar fossae. Three stages of canal development were identified based on the length of canals and on characteristics of chondrocytes and matrix surro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
1

Year Published

1987
1987
2007
2007

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 33 publications
4
41
1
Order By: Relevance
“…These cells resorb the cartilaginous matrix and open the lacunae of adjacent chondrocytes. Previous studies have reported similar results where mononuclear or TRAP-positive cells (tartrate-resistent acid phosphatase) are present in the same position (Cole and Wezeman 1985;Chappard et al, 1986;Á lvarez et al, 2005a,b). The resting chondrocytes immediately in front of the apical tips show morphological evidence of cell death and also display active caspase 3 reactivity, thus confirming previous observations in the rat tibia where chondrocytes seemed to degenerate during canal formation (Lee et al, 2001).…”
Section: Formation Of Cartilage Canals and Bone Development In The DIsupporting
confidence: 68%
See 4 more Smart Citations
“…These cells resorb the cartilaginous matrix and open the lacunae of adjacent chondrocytes. Previous studies have reported similar results where mononuclear or TRAP-positive cells (tartrate-resistent acid phosphatase) are present in the same position (Cole and Wezeman 1985;Chappard et al, 1986;Á lvarez et al, 2005a,b). The resting chondrocytes immediately in front of the apical tips show morphological evidence of cell death and also display active caspase 3 reactivity, thus confirming previous observations in the rat tibia where chondrocytes seemed to degenerate during canal formation (Lee et al, 2001).…”
Section: Formation Of Cartilage Canals and Bone Development In The DIsupporting
confidence: 68%
“…Á lvarez et al (2005b) reported that several of these cells are released as viable cells into the canal cavity and finally might differentiate into boneforming cells. Similarly, freeing of chondrocytes from the matrix surrounding cartilage canals was proposed by Cole and Wezeman (1985). In contrast, other studies suggested that elongation of canals causes death of resting chondrocytes (Roach et al, 1998;Lee et al, 2001).…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations